THREAT STATUS AND CONSERVATION PRIORITY FOR THE ICHTHYOFAUNA OF THE RIVER GOMTI IN THE LUCKNOW REGION - Dr. Shailendra Kumar Singh (International Journal of Innovations in Engineering Research and Technology, 2016)
It was decided to carry out this study to find out more about the present situation of the rapidly diminishing icthyo-faunal biodiversity in the Gomti River, which is a Ganges tributary in the Lucknow region that extends for around 940 kilometers. In this study, 56 species belonged to 41 genera and nine orders, and 21 families were discovered, according to the results. The Cyprinidae order contained the greatest number of species (33.91 percent), followed by the Siluridae (30.32 percent), the Ophiocephaliformes (5.37 percent), the Mastacembeliformes (3.59 percent), the Clupeiformes (3.59 percent), the Mugiliformes (1.79 percent), the Beloniformes (1.79 percent), and the Tetraodontiformes (1.79 percent (1.79 percent ). According to the International Union for Conservation of Nature, more than half of the species (46), which include the Ompok bimaculatus, Ompok pabda, and Wallago attu, Bagarius bagarius, and Ailia coila, are classed as Least Concern (Least Concern) (IUCN). Several foreign species, including Cyprinus carpio, Ctenopharyngodon idellus, Oreochromis mossambicus, and Hypophthalmichthys molitrix, were eliminated from the research due to a lack of accessible data. Fishes from three different sample sites along the Gomti River in the Lucknow Region were found to have statistically significant (p 0.05) Simpson diversity indexes, fish species richness, and fish abundance.